Towards a simplified approach to the modelling of the star-like molecule fluids - Duda, Yu.; Trokhymchuk, A. (Condensed Matter Physics, 2002)
A theoretical approach to considering a wide spectrum of equilibrium properties
of fluids formed from the four-branched molecules (e.g. four-arm star
polysterene samples, four-arm block copolymers, etc.) is presented and
discussed. The proposed approach is within the framework of an associative
version of integral equation theory and is based on an analytical
solution of the four-site associative hard-sphere model. Results and discussion
are explained by the comparison against Monte Carlo computer
simulation data generated for a freely-joined tangent hard-sphere model of
a star-like molecule fluid. It is shown that the proposed theory works well for
the star-like molecule fluids in homogeneous phase where it predicts the
structure for molecules with relatively long arms and at high densities. The
obtained results qualitatively reproduce the most important experimental
features of the solvation force induced between two macrosurfaces due to
the presence of star-like aggregates. Запропоновано теоретичний підхід до вивчення широкого спектру
рівноважних властивостей рідин, молекули яких мають форму зірок
(як наприклад полістирен, та ряд кополімерів). Підхід у своїй основі ґрунтується на аналітичному розв’язку, отриманому в теорії інтегральних рівнянь для так званої асоціативної моделі силових центрів.
Результати та висновки з теоретичного підходу підкріплені порівняннями з комп’ютерним експериментом, проведеним для моделі гнучких полімерів, що мають форму зірок. Показано, що запропонований
теоретичний підхід працює добре для однорідної фази, де добре відтворює структурний фактор для відносно довгих кінцівок зірки і високих густин рідини. Отримані результати відтворюють найважливіші характеристики сольватаційної сили між двома плоскими поверхнями, зануреними у розчин з наявними зірковими молекулами, що
спостерігається у лабораторному експерименті.